An Examination of Non-Traditional Approaches to Liquefying Natural Gas - Onuoha Fidelis Wopara; Nnadikwe Johnson (Journal Majelis Paspama, 2026)
Liquefied natural gas (LNG) plays a vital role in the energy industry due to its high energy density, low carbon footprint, and ease of transportation. The emergence of unconventional natural gas resources is reshaping the LNG landscape, requiring specialized liquefaction approaches. This review examines non-traditional approaches to liquefying natural gas, focusing on coalbed methane, synthetic natural gas, LNG-FPSO, and pressurized liquefied natural gas (PLNG). We analyze the unique characteristics and challenges of these processes, highlighting recent advancements in design and optimization. Coalbed methane liquefaction, for instance, requires efficient methane separation and oxygen removal techniques. Synthetic natural gas liquefaction involves optimizing methanation reactions and integrating with existing infrastructure. LNG-FPSO technology addresses space constraints and sloshing conditions on offshore platforms. PLNG offers a compact solution with pressurized storage, enhancing CO2 solubility and reducing equipment footprint. The shift towards unconventional gas sources demands innovative liquefaction solutions. Key areas of development include advanced separation technologies, compact and safe process designs, and enhanced heat transfer mechanisms.